1999
DOI: 10.1073/pnas.96.11.6336
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for membrane lymphotoxin in natural killer cell development

Abstract: Development of natural killer (NK) cells is thought to depend on interactions between NK progenitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 26 publications
3
77
3
Order By: Relevance
“…While this manuscript was in preparation, impaired function of NK cells in LT␣ Ϫ/Ϫ mice was reported (58,59,63), consistent with the possibility that NK and NK T cells share a common precursor. The precise details of the process by which LT affects NK cells remain controversial.…”
Section: Discussionsupporting
confidence: 62%
“…While this manuscript was in preparation, impaired function of NK cells in LT␣ Ϫ/Ϫ mice was reported (58,59,63), consistent with the possibility that NK and NK T cells share a common precursor. The precise details of the process by which LT affects NK cells remain controversial.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, it appears that there are some factors released by stroma that could be important for the fi rst steps of induction towards NK cells lineage but acquisition of receptors seems to be independent of stroma signals. Some published data refers that NK cells receptors are acquired in an orderly and nonrandom manner during in vitro human NK cell differentiation (Miller & McCullar, 2001;Mrozek, Anderson, & Caligiuri, 1996;Grzywacz et al, 2006) and, differing from our results, indicated that the fi rst inhibitory receptor to be surface-expressed is CD94/NKG2A while KIRs appear only later and in low percentages (Briard, Brouty-Boye, Azzarone, & Jasmin, 2002;Iizuka et al, 1999;Grzywacz et al, 2006;Miller & McCullar, 2001). Cytotoxicity results were consistent with the phenotypic behavior implying that these NK cells can demonstrate specifi city in the recognition process.…”
Section: Differentiation Of Natural Killer Cells From Human Umbilicalcontrasting
confidence: 34%
“…In line with this, mice lacking LNs due to knockout of the helix-loop-helix inhibitor Id2 gene (Id2 Ϫ/Ϫ ) are deficient in NK cells but not T or B lymphocytes (7). Moreover, lymphotoxin ␣ (Lta)-deficient mice show impaired LN organogenesis and defective NK cell development (8). However, none of these observations provides incontrovertible evidence that LNs are significant sites of NK cell differentiation or development.…”
Section: T Regulatory Cells Control Numbers Of Nk Cells and Cd8␣mentioning
confidence: 80%